2013
DOI: 10.1080/1357650x.2012.744414
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Geschwind's hypothesis on brain lateralisation: A functional MRI study of digit ratio (2D:4D) and sex interaction effects on spatial working memory

Abstract: The Geschwind-Behan-Galaburda (GBG) hypothesis links cerebral lateralisation with prenatal testosterone exposure. Digit ratio measures in adults have been established as potential markers of foetal sex hormonal milieu. The aim of the study was to evaluate the sex-dependent interaction of digit ratio measures and cerebral lateralization as well as their neurohemodynamic correlates using functional MRI (fMRI). Digit ratio measures-ratio of index finger (2D) length to ring finger (4D) length (2D:4D) and differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Because handedness emerges as a stable trait early in life (e.g., Hepper, Wells, & Lynch, 2005), this observation suggests that DR-L is a marker of fundamental variations in lateralized brain function. Consistent with this, Kalmady et al (2013) found in a brain-imaging study that lower (i.e., more negative) DR-L was associated with more right-hemispheric activation. These observations are also generally consistent with findings documenting that high testosterone prenatally is associated with asymmetric brain development in favor of the right hemisphere (Geschwind & Galaburda, 1987).…”
supporting
confidence: 63%
“…Because handedness emerges as a stable trait early in life (e.g., Hepper, Wells, & Lynch, 2005), this observation suggests that DR-L is a marker of fundamental variations in lateralized brain function. Consistent with this, Kalmady et al (2013) found in a brain-imaging study that lower (i.e., more negative) DR-L was associated with more right-hemispheric activation. These observations are also generally consistent with findings documenting that high testosterone prenatally is associated with asymmetric brain development in favor of the right hemisphere (Geschwind & Galaburda, 1987).…”
supporting
confidence: 63%
“…Therefore, this task was coded as a distinct category under the label Btoken.^The n-back task also is a well-known measure of working memory, although it might be more readily associated with verbal working memory. In an example of a visual-spatial working memory version of the n-back task, Kalmady et al (2013) asked participants to identify the location of the dot that changed color immediately after it was presented (0 back) or two trials before (2 back). Considering that the direction of sex differences can vary as a function of task, specific task is a potentially important moderator of sex differences in visual-spatial working memory that was coded in the present analysis.…”
Section: Identifying Potential Moderatorsmentioning
confidence: 99%
“…These speculations have no empirical support within gifted boys and cannot be considered plausible explanations. Although, Kalmady et al (2013) evaluated the sex-dependent interaction of digit ratio measures and cerebral lateralization and they reported that men had significantly less bilateral 2D:4D than women, and their findings support the concept of higher prenatal testosterone linked with higher laterality (Kalmady et al, 2013).…”
Section: Discussionmentioning
confidence: 70%